The Relation of Emotional Maturity, Family Interaction and Marital Satisfaction of Early Age Married Couples (Journal of Family Sciences, 2019)
Early marriage is a marriage carried out by couples less than 20 years old. The aim of this study was to analyze the relationship and the influence between emotional maturity and family interaction on marital satisfaction in early married families. Examples in this study are families who married early age selected by way of purposive sampling amounted to 30 people. The research was conducted in Bojong Gede Village, Bojong Baru Village, Rawa Panjang Village, Ragajaya Village and Pabuaran Village, Bojong Gede District, Bogor Regency. The results showed that husband and wife age at married, income per capita, emotional maturity and family interaction had a positif significant relationship with marital satisfaction, but famiy size and age of marriage had a negatif significant relationship with family satisfaction. Husband age faktor and family interaction have positif effect to marriage satisfaction, but education level of husband and age of marriage have negatif effect to marriage satisfaction.